Evaluating Influencer Marketing Perception Among Gen Z on Instagram - Abdulgalejeva, Renata; Král, Petr, 1979-; Průša, Přemysl, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
As the Gen Z population becomes increasingly active in purchasing products, it is important for businesses to understand how to effectively promote their product towards this demographic. Each generation has unique characteristics distinguishing them, presenting new challenges and also opportunities for businesses to explore when it comes to advertising towards the Gen Z population. The purpose of this thesis is to examine the advertising avoidance of Gen Z and effectiveness of advertising in the context of social media influencer marketing. An online questionnaire was distributed via Instagram utilising snowball sampling. It obtained responses from a total of 107 participants, 56 of whom were identified as Gen Z. The collected data allowed for comparisons to be made between the Gen Z and non-Gen Z sample. Overall, the results indicate that while a majority of respondents express distrust towards influencers’ product recommendations, Gen Z users still continue to engage in sponsored giveaways and utilize discount codes promoted by influencers. Further, for Gen Z, congruence between an influencer’s image and what they promote is important. Although Gen Z appear to have more moral values, these do not necessarily have an influence on their purchasing decisions; they may disapprove of controversial influencers participating in advertising campaigns, but will still purchase products from brands with unethical stakeholders.
Vedoucí práce: Petr Král
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses